The dragonslayers - Coville, Bruce; Coville, Katherine (New York : Aladdin Paperbacks, 2002)
A brave squire, an earnest page, and a strong-willed princess set out, each for individual reasons, to try to slay the dragon created to carry out a witch's revenge.
4.6
3-6.
3-6
Keywords: Dragons -- Juvenile fiction; Princesses -- Juvenile fiction; Dragons -- Fiction; Fantasy; Princesses -- Fiction; Dragons -- Fiction; Princesses -- Fiction; Fantastic fiction; Fantastic fiction